Social capital and lifestyles: a review of the literature (Revista Venezolana de Salud Pública, 2018)
ABSTRACT Currently many studies suggest that social capital is a key determinant of physical and psychological health in the population; however little is known about the relationship between this and the behaviors associated with lifestyles. The aim of this study is to identify, through a review of the literature, the empirical evidence that assesses the relationship between social capital and behaviors associated with lifestyles. Original sources in English, Spanish and Portuguese of the databases were reviewed: Pubmed, Scielo, Ebsco, Google Scholar and Sciencedirect between the years 2000 and 2017; was using the following descriptors: social capital, lifestyles and health behaviors. The final sample consisted of thirty-six articles. The findings suggest that social capital is related to all the factors associated with lifestyles to a greater or lesser extent. Studies support the idea that social participation, social support networks, social trust and membership as elements of social capital have a significant influence on lifestyles, hence the important of incorporating it in future programs and interventions of health promotion.
Keywords: social capital; lifestyles; health promotion